DAMPAK PENARIKAN DIRI AMERIKA SERIKAT DARI PARIS AGREEMENT 2015 TERHADAP PENDANAAN KELOMPOK LEAST DEVELOPED COUNTRIES: The Impact of the United States’ Withdrawal from the Paris Agreement 2015 on Funding for the Least Developed Countries - Herawati Dwicahyani; Amalia Zuhra (Reformasi Hukum Trisakti, 2026)
The United States' withdrawal from the 2015 Paris Agreement, under Donald Trump's administration, for the second time has caused uncertainty for global climate governance, particularly in relation to funding for the Least Developed Countries (LDCs). The research questions are: what factors caused the United States to withdraw from the 2015 Paris Agreement, and what impact did the United States' withdrawal from the 2015 Paris Agreement have on the climate funding scheme for LDCs? The research method employed is a normative juridical and descriptive analytical approach, utilizing secondary data, and the data are analyzed qualitatively. The results of the discussion and conclusions show that the United States is one of the largest contributors to the Green Climate Fund (GCF) and a key actor in climate finance negotiations, having a strategic process for the sustainability of mitigation and adaptation projects in LDCs. The uncertainty of the United States' commitment, both due to its withdrawal from this agreement and the lack of an explicit statement regarding its contribution within the framework of the New Collective Quantified Goal on climate finance (NCQG), will have implications for increased funding risks and hamper energy transition efforts and the strengthening of climate adaptation capacity in LDCs.